Preparation of the oligochitosan-silver nanoparticles with a potential application as an antigungal fertilizer against Fusarium oxysporum causing fusarium wilt disease on tomato - Vũ, Nguyễn Thanh; Quyền, Huỳnh; Xô, Dương Hoa; Luân, Lê Quang (Vietnam Journal of Biotechnology, 2018)
Chitosan with molecular weight (Mw) approx. 573,2 kDa and deacetylation degree about 80% was irradiated by gamma rays at swollen state in the present of 1 - 3% hydrogen peroxide for degradation to prepare low Mw products. The solution of 5% low Mw chitosan in 0.5% acetic acid was further irradiated for induction of oligochitosan. The obtained results indicated that the foliar application by 100 ppm oligochitosan with Mw ~ 19.5 kDa prepared by 4kGy-irradiation of the low Mw chitosan with Mw ~ 48.4 kDa had a strongly growth promotion effect on tomato plants after 30 days cultivation. The oligochitosan silver nanoparticles (AgNPs) was also synthesized by gamma irradiation of solution contained 5% low Mw chitosan and 1 mM silver nitrate in order to prepared antifungal fertilizer for tomato plants. The results on in vitro test for the antifungal activity oligochitosan AgNPs against Fusarium oxysporum causing Fusarium wilt disease pointed out that the addition of this product into cultivated media inhibited strongly the growth of the Fusarium oxysporum pathogen fungus on carrot agar media. The antifungal efficiency values were found from 50.5 to 94.9% by the supplementions of silver concentrations from 20 to 30 ppm, respectively. The supplementation with a silver concentration of 40 ppm inhibited completely the growth of F. oxysporum on the cultivated media. Thus the oligochitosan AgNPs product had not only the growth promotion activity for tomato, but also high antifungal activity against F. oxysporum. This product is promising to be used as an antifungal fertilizer for tomato with safety and efficiency.